Seed dormancy in germplasm collection of rice (Oryza sativa) insensitive to photoperiod - KALITA, U C; BARUAH, D K; UPADHAYA, L P (The Indian Journal of Agricultural Sciences, 2013)
Field evaluation of 212 photoperiod-insensitive germplasm collection of rice (Oryza saliva L.) during autumn seasons of 1990 and 1991 revealed that 155 collections had no seed dormancy. The seed dormancy in 57 collections ranged from 7 to 30 days. 'Cheni Abu' showed the highest dormancy period (30 days), followed by 'As 326', 'Goalbhog', 'Banglami' and 'Bala'. In 21 indigenous Collections it was observed both under field and laboratory conditions. 'Cheni Ahu', 'Goalbhog' 'Nilajee', 'Banglami', 'As 229', 'As 93-1'. 'Guni Ahu'. 'Rongadoria 4'. 'Basmati Culture' and 'Podumani Ahu' were identified promisingdonors for seed domancy. Correlation study showed significant positive correlation with plant heightand lodging score. Field as well as laboratory methods were found neCessary for identification of dormant rice germplasm collections. Seed dormancy of the indigenous germplasm collections appears to be an adaptive mechanism for their survival in the hot, humid rainy season.